(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
The new Insolvency Act sets down the presupposition identified with insolvency. The apparent conceptual homogeneity of such conceals a split associated with the mode in which proceedings are brought (involuntary and voluntary bankruptcy). This study explores the relationship between insolvency and its warning signs, highlighting the difficulty concerning probative evidence as well as the application of both notions for the interested parties and the judge.